Arus Balik Pesantren: Reharmoni Pesantren dan Kebudayaan Jawa - Rofiq Hamzah (Lembaga Kajian dan Pengembangan Sumberdaya Manusia, 2021)
At the early development of pesantren, the Islamic’s pattern were presented according to the Islamic pattern was developing at that time which was integrated with Javanese culture. Santri wear traditional Javanese clothes; learn Islamic text which is written in Javanese script and language in primbon, suluk and wirid formats. Suluk is the teaching of Sufism which is packaged in verses of the Macapat song, so santri get used to learning through Javanese songs. The intimacy between pesantren and Javanese culture was broken after post-Dipanegara’s War polarization, which divided the religious patterns of Javanese society into three groups: priyayi, putihan and abangan. The three of them were pushed to show their different identities and cultural expressions. In this context, pesantren is getting close to the Arabic culture. Meanwhile, Javanese culture is identified with priyayi and abangan. The peak of this polarization was when Javanese culture was taken over by abangan groups affiliated with the PKI for propaganda purposes. As a result, pesantren moved away from Javanese culture. Positive changes happened when Islam Nusantara became the PBNU’s platform and the strengthening of religious moderation by the Ministry of Religion, where appreciation for local culture was an important part. Slowly pesantren began to open up to Javanese culture. The appearance of several pesantren’s kiai in Javanese clothing, the emergence of Javanese-Islamic manuscript studies and the systematic efforts made by some of pesantrens to rebuild closeness to Javanese art, including those carried out by the Pesantren API Tegalrejo, Magelang and Pesantren Kaliopak, Bantul, indicate reharmony between pesantren and Javanese culture. This paper aims to capture the dynamics of pesantren and Javanese culture relations from its beginning to its current condition.